ՀՀ տեղեկատվական անվտանգության մարտահրավերները արդի փուլում - Աղայան Նարինե (YSU Journal of International Affairs, 2017)
In the current phase of the information revolution, under the conditions of formulating information society, issue of information security is increasingly getting an important designation. Along with their huge advantages, brought forth new forms and means of communication, spreading quickly, give birth and will be giving new threats and challenges. Ensuring the information security has become a matter of national security. The article is an attempt to represent the Republic of Armenia’s domestic and international developments in the context of the global dimension of the challenges facing the sector of information security, the resolution of which is necessary for the national security support of the republic.